Enabling agricultural transformation through climate change policy engagement - Kuntashula, E.; Chibwe, T.; Chabala, L.M. (Elsevier, 2017)
Climate change effects are evident in agriculture and hence climate-smart approaches are gaining ground in southern Africa. Governments are beginning to respond by putting in place the required policies guiding investment, development, and building long-term adaptive measure in production systems. Subregional organizations and international organization including the United Nations are among the leaders in shaping the policy discussions that are going on. Although most countries have good agricultural policies in place there are some that require alignment of especially institutional arrangements to capture climate change mitigation and adaptation strategies. Investment toward the achievement of climate-smart agriculture practices needs to be improved. The involvement of all stakeholders including the private sector and farmers in shaping climate change-related policies needs to be enhanced. The aim of this chapter is to discuss and evaluate policies that are suitable for the countries in the region to fully unleash climate-smart approaches and technologies.